KAJIAN PEROLEHAN KARBON SEBAGAI DAMPAK INTERVENSI KASUS: EKS-PLG BLOK A, MENTANGAI, KALIMANTAN TENGAH(CARBON RESULT STUDY AS INTERVENTION IMPACT, CASE: EKS-PLG BLOCK A, MENTANGAI, CENTRAL BORNEO) - Sri Rahaju; . Istomo (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
CCFPI is project activity on “Climate Change, Forests and Peatlands in Indonesia” funded by the “Canadian International Development Agency” (CIDA) through Climate Change and Development Fund, Canada. This project is designed to increase sustainable management of forests and peatlands in Indonesia in order to increase the capacity in carbon sequestration and also better of community incomes. One of project location in Kalimantan is area Ex-PLG Blok A, Mentangai, Central Kalimantan. This article present study on total value carbon gained as impact from various interventions in location of CCFPI project activity in area Ex-PLG Blok A, Mentangai. Method of estimation on carbon stock is conducted by Sample Plot of Measurement (PCP). Calculation of carbon stock with equation of alometrik which is present in Field Guidance to Estimate Carbon Stock on Peatland (Murdiyarso et.al., 2004). Activity of cannal blocking by CCFPI project has result to the positive impacts to the reduction rate of carbon both for above and below ground carbon as well as carbon content by tree plantation established by the community inside the areas of around 43,451 ha. Based on result of calculation, the amount of above ground carbon stock obtained 14,448 ton C. Carbon stock found in the trees plantation in surrounding the cannal 0.777 ton C. Below ground carbon stock is ranged between 550,782 ton C up to 2,223,424 ton C.